Effectiveness of entomopathogenic fungal combinations on eggs and larval development of Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) in corn plants - Indri Yanil Vajri; Trizelia Trizelia; Haliatur Rahma; Yusniwati Yusniwati (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2026)
Spodoptera frugiperda J.E. Smith is an invasive pest of corn, requiring effective and environmentally friendly control strategies. This study aimed to evaluate the effectiveness of three entomopathogenic fungal (EPF) isolates, namely Beauveria bassiana WS, Metarhizium anisopliae B22C, and Trichoderma asperellum A116, tested as single isolates or in combination against S. frugiperda eggs and larvae. The experiment used a Completely Randomized Design (CRD) with eight treatments (three single treatments, four combinations, and a control) and four replications. Conidial suspensions were applied by spraying onto eggs and second-instar larvae. Parameters observed included the percentage of unhatched eggs, larval mortality, and pupal and adult development. Chitinase, protease, and lipase activities were qualitatively tested to support the identification of pathogenicity mechanisms. Data were analyzed using analysis of variance (ANOVA), followed by the LSD test at a 5% significance level. The results showed that EPF combinations increased mortality and inhibited the development of S. frugiperda. The combination of B. bassiana WS + T. asperellum A116 was the most effective treatment, inhibiting egg hatching by 85% and reducing pupal and adult formation to 25.95% and 12.96%, respectively. The highest mortality of first-instar larvae was observed in the single treatment of B. bassiana WS and the tertiary combination of B. bassiana WS + M. anisopliae B22C + T. asperellum A116, at 24.18% and 22.91%, respectively. Consistent enzymatic activity indicated potential biocontrol synergy through the production of cuticle-degrading enzymes. This combination is recommended for field-scale testing as an environmentally friendly alternative to reduce dependence on chemical insecticides.